Formation of Japan’s image in Central Asia - Ашинова, Ж. Е. (Journal of Oriental Studies, 2017)
At the present time, it is possible to observe the dynamic rates of development of the relationship between Japan and the countries of Central Asia. And this concerns the political, diplomatic, trade and economic, cultural and educational spheres of cooperation between the parties. Japanese companies are actively investing in various sectors of economic and economic development, еspecially in the sphere of reconnaissance and extraction of natural resources and energy. At the same time, it is important to keep in mind the rich and advanced experience of Japan in the field of modern technologies and the development of human resources, the study and use of which will be of great benefit in the further development of the countries of Central Asia. Between Japan and the countries of Central Asia there are no major contradictions and problems of a fundamental nature. Nothing hinders active mutual cooperation. apan has a positive image and a high degree of confidence in this region. This article examines Japan’s policy in Central Asia, which contributed to the formation of a positive image of Japan.